ADVOCACY IMPLEMENTATION, COMMUNICATION, SOCIAL MOBILIZATION IN THE HEALTH DEVELOPMENT PROGRAM. [A THEORETICAL REVIEW] - Muh. Zainal S. (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2019)
Health problems become responsibility of all elements of society, not only  government.  Support and involvement from all  stakeholders are crtitical to overcome  many of health problems in the context  of development and social change.  This  article  aims  to  produce  descriptive  theoretical  advocacy,  communication,  social  mobilization  and research findings that are relevant to Advocacy, Communication and Social Mobilization (AKMS). This study used a literature study approach (desk study) by collecting documents and literature relevant  to the topic of the article. Based on literature studies, it can be concluded that advocacy, communication and social mobilization activities are interrelated.  Advocacy  is  an  approach  to  securing  economic  resource  needs  and  policy  changes,  by  influencing stakeholders,  the  private  sector,  community  elements,  including  the  media.  Meanwhile,  communication  seeks  to increase awareness, influence social norms, create changes in the behavior of individuals or a community through communication  channels  both  interpersonal  (counseling),  mass  media  and  the  internet  including  social  media. Furthermore,  social  mobilization  is  concerned  with  efforts  to  gather  social  support  to  change  norms,  improve services, expand community support and solve social problems. Keywords: Advocacy, Communication, Social Mobilization